The Role of Small-Scale Household Power Plants in the Electricity Supply by the Hungarian Settlements - Kulcsár, Balázs (International Journal of Engineering and Management Sciences, 2018)
The utilization of renewable energy sources spread with stormy speed on the world therefore more and more municipalities propose that they satisfy their energy demand from renewable sources. The fossil fuels represent a significant proportion in Hungarian energy balance and the majority of these is import energy. The proportion of renewable energy sources must be increased to decrease the energy dependence and the energy cost of municipalities, to increase the energy security and to consider the aspects of environment.The interest of Hungary is to increase the proportion of renewable energy sources in energy supply. In order to this, the government created the small-scale household power plant (SSHPP) category in the Electricity law. This power plants should be not greater than 50 kW’s performance. In this category, electricity can be produced from renewable and fossil sources. Since the government introduced the small, household size power plant category the installed capacity was grown quickly in the last seven years. The general capacity was 0.51 MW altogether at the end of year 2008 but it has already approached 129 MW’s at the end of year 2015. The general capacity was increased by the multiple of the previous year every year between 2008 and 2015 and there will be more a dynamic capacity expansion. Data about the capacity and the produced electricity can be displayed on municipality level, too. The purpose of the investigations is to determine: how can the built capacity of the small, household size power plant category participates in the electricity supply of the Hungarian settlements? So how many percentages of electricity demand can be gratified by this electricity power on the settlements? Based on this a ranking can be made among municipalities which shows the level of sufficiency in production of renewable energy and give a possibility for the power shift. Finally, to what extent can be built upon this power plant category in order to that Hungary can comply its objective value.